Aftershock Patterns in Recent Central Apennines Sequences. Issue 4 (9th April 2019) - Sebastiani, G.; Govoni, A.; Pizzino, L.
Abstract: During the last 20 years, three seismic sequences affected the Apenninic belt (central Italy): Colfiorito (1997–1998), L'Aquila (2009), and Amatrice Visso‐Norcia Campotosto (2016–2017). They lasted for a long time, with a series of moderate‐to‐large earthquakes distributed over 40‐ to 60‐km‐long Apenninic‐trending segments. Their closeness in space and time suggested to study their aftershock sequences to highlight similarities and differences. Aftershock space migration and the distribution of aftershock interarrival times were studied. Mathematical Morphology and nonparametric statistics were applied to reduce the effect of spatial noise. Parametric analysis in time domain and spectral analysis were performed. Two different types of aftershock sequences were found. The L'Aquila sequence presented a continuous and periodic temporal variation (period ≃120 days) of aftershock activity center along the sequence axis, while the other two sequences showed a piecewise continuous pattern and a shorter duration. We also found two different types of temporal evolution of the mean radial distance between the aftershock hypocenters and the one of a reference event corresponding to the start of a large and fast increase of daily energy release. One type was well described by a simple exponential model, while a power law model was more appropriate for the other one. Furthermore, in the first case, the aftershock interarrival time was very well fitted by an exponential model, while noticeable deviations were present in the other case. A possible explanation was provided in terms of the local geological and hydrogeological properties, which depend on the region location with respect to the Ancona‐Anzio tectonic lineament. Key Points: Two different temporal patterns of aftershock migration along sequence axis were found The type of pattern is possibly correlated with the local lithological and hydrogeological properties